Composição, estrutura e aspectos ecológicos da mata ciliar do Rio Araguari no Triângulo Mineiro - Rodrigues, Victor Hugo Paula (2007)
The study aimed to characterize the tree-shrub community of a riparian forest, one of the last remnatns on the Araguari River, at Uberlândia, Triângulo Mineiro region, Minas Gerais State. The composition, horizontal and vertical structure were investigated by phytosociological survey of 110 plots of 10m x 10m (1,1ha). All trees with CAP ` 15 cm were registered. There were sampled 1.393 trees distributed in 89 species and 36 families. Hirtella gracilipes (Hook.f.) Prance was the most abundant specie, with the highest frequency, density and VI. It is a small tree specie, predominant in the understory of the forest. The Shannon index was H = 3,65 nats.ind-1. The most common soil in the study area was classified as Litholic Neosol dystrophic, with gneiss rock outcrops, and in some parts of the forest there were soils of the Haplic Cambisol Tb dystrophic type. The floristic comparisons indicated the riparian forest of Araguari river is more similar to the Triângulo Mineiro forests, to riparian forest in Três Marias, MG, and to gallery forests of the Central Brazil, than to riparian forests of southsoutheast of Minas Gerais and São Paulo. The analysis of maximum, medium and minimum heights of the species showed the forest has three vertical strata. The stratum 1 (1,5m > h ` 10m) had the highest richness, density and was represented by a group shade-tolerant and light-demanding understory species. There were also individuals juvenile of species belonging to the higher strata, classified as light-demanding canopy species. The stratum 2 (10m > h ` 15m) occupied the largest part of the study area, and was considered mostly a intermediate stratum, including canopy species as well as some understory mature trees. The stratum 3 (h > 15m) had the lowest density and the species which form this part of the forest have far greater number of individuals in inferior strata. This indicates the forest is recovering from anthropic disturbance suffered in the past. The presence of a major quantity of animaldispersed species and individuals emphasizes the important preservation of this riparian forest for the fauna of Araguari River Valley and whole region.